Early Ordovician conodonts from Cow Head Peninsula, western Newfoundland. - Stouge S.; BAGNOLI, GABRIELLA (1988)
This paper presents taxonomical description of latest Tremadocian to Middle Arenigian conodonts recovered from the Ledge-Point of Head Section /Cow Head Group) on the southwestern shore of Cow Head Peninsula, western Newfoundland. 20 samples have been collected yielding about 18.000 conodont elements. 42 genera and 75 species are present. New genera and new species are described. The conodont fauna comprises species both from the Micontinent "Province" and the North-Atlantic "Province". Refinements to the current zonation available for the North Atlantic "Province" on the basis of species of Prioniodus are suggested. Three transgressive-regressive events have been recognized and correlated with the faunal succession. The evolutionary history of Prioniodus and Oepikodus is suggested.